2013
DOI: 10.1177/0950017013481084
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the interplay between Buddhism and career development: a study of highly skilled women workers in Sri Lanka

Abstract: Exploring the interplay between Buddhism and career development: a study of highly skilled women workers in Sri LankaThis article adopts a socio cultural lens to examine the role of Buddhism in highly skilled women workers' careers in Sri Lanka. While Buddhism enabled women's career development by giving them strength to cope with difficult situations in work, it also seemed to restrict their agency and constrain their career advancement. Based on our findings, we argue that being perceived as a good Buddhist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…I am the manager of the team, after all (Akila) Akila speaks in ironic terms (Potter, 1996) of the claim that diversity enhances fairness in the organisation. He draws on well-known broad cultural ideas of 'karma' (Fernando and Cohen, 2013) to enable his audience to better appreciate the emotional dilemmas he experiences as he is compelled to overlook more deserving candidates in order to implement the genderbased quota. After refuting the organisation's diversity agenda, Akila goes on to explain how he refuses to cooperate with diversity initiatives in the spirit of not encouraging unfair practice: Highlighting the contradictions in discourses of diversity provides space for Akila to refuse to cooperate with the diversity agenda (Ainsworth and Hardy, 2004) and position himself in a more agentic manner in the process.…”
Section: Share My View With Many Others -I Have To I Felt Guilty Fmentioning
confidence: 99%
“…I am the manager of the team, after all (Akila) Akila speaks in ironic terms (Potter, 1996) of the claim that diversity enhances fairness in the organisation. He draws on well-known broad cultural ideas of 'karma' (Fernando and Cohen, 2013) to enable his audience to better appreciate the emotional dilemmas he experiences as he is compelled to overlook more deserving candidates in order to implement the genderbased quota. After refuting the organisation's diversity agenda, Akila goes on to explain how he refuses to cooperate with diversity initiatives in the spirit of not encouraging unfair practice: Highlighting the contradictions in discourses of diversity provides space for Akila to refuse to cooperate with the diversity agenda (Ainsworth and Hardy, 2004) and position himself in a more agentic manner in the process.…”
Section: Share My View With Many Others -I Have To I Felt Guilty Fmentioning
confidence: 99%
“…We also acknowledge the possibility that Buddhism and skilful means may be commoditized in organizational and leadership discourse. A study by Fernando and Cohen (2013: 1034) in Sri Lanka found that women enacted Buddhism in a very public and individualistic way so that they could buffer gender discrimination “when good Buddhist women were chosen for leadership positions reserved for male candidates since they were perceived as having the potential to pass on moral values to their subordinates”. Therefore, Buddhism can be used as a gender management strategy or to craft desirable work identities (Lynch, 1999; Radhakrishnan, 2009) to help not only followers but also leaders themselves (Kemavuthanon and Duberley, 2009).…”
Section: Responding To Criticism Of the Dark Side Of Leadership And Omentioning
confidence: 99%
“…The outer layers highlight institutional and societal barriers. The model, therefore, suggests that career barriers may be classified into those that are individual, organizational and societal in nature (Akpinar-Sposito, 2013; Amondi, 2011; Fernando & Cohen, 2011; Neidhart & Carlin, 2003).…”
Section: Conceptualization Of Barriers To Career Advancement Of Womenmentioning
confidence: 99%
“…A few studies in Sri Lanka have delved on women’s experiences with career advancement (Bombuwela & De Alwis, 2013; Fernando & Cohen, 2011; Silva, 2008). One found that gender discrimination, gender stereotyping and conflicting demands from family and work were inhibiting career advancement of Sri Lankan women in both public and private sectors (Silva, 2008).…”
Section: Conceptualization Of Barriers To Career Advancement Of Womenmentioning
confidence: 99%
See 1 more Smart Citation